PENGARUH PENERAPAN GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR PERTANIAN - Nurlaeli, Fenti; Prayoga, Teguh Dwi (Program Studi Akuntansi, Universitas Kuningan, 2025)
Abstract This study aims to look at the effect of implementing green accounting and environmental performance on the financial performance of agricultural sector companies listed on the IDX for the 2021-2023 period. The research method uses a causal quantitative approach. The population is agricultural sector companies listed on the IDX. A sample of 8 companies was taken by purposive sampling. Data analysis techniques using SPSS. The results showed that green accounting has no effect on financial performance, this is evidenced by the results of the t test 0.868>0.05. environmental performance has no effect on financial performance. This is evidenced by the results of the t test 0.928>0.05. While simultaneously green accounting and environmental performance have a significant effect on financial performance. This is evidenced by the results of the f test 0.007 <0.05. Future research is expected to better understand the relationship between green accounting, environmental performance, financial performance in various contexts. Companies need to practice green accounting and environmental performance as a whole in business strategy, in the hope that investors will be more interested and support the adoption of sustainable business practices. Keywords: Green Accounting, Environmental Performance and Financial Performance